Examining the Digital Revolution in Religious Education: A Bibliometric Exploration of Crises, Opportunities, and the Future of Research 2009-2025 - Nabila, Inatsa Zulfa; Inayati, Nurul Latifatul; Yuzarni, Silvani; Salim, Muhammad Fathi (Universitas Muhammadiyah Surakarta, 2025)
This study uses bibliometric analysis to explore research on digital technology–based religious learning from Scopus-indexed publications between 2009 and 2025. The growth of technology, accessibility of digital devices, and learning innovations have driven increasing research output, while challenges such as low digital literacy, technological barriers, and online misinformation remain key issues. By analyzing 133 English-language journal articles with Scopus Analyzer, R, RStudio, and VOSviewer, this study identifies research trends, effectiveness, and challenges in integrating digital technology into religious education. Results show a significant rise in publications from 2019 to 2025, indicating growing academic and practical interest. Indonesia contributed the most publications, with Malaysia showing strong international collaboration. Thematic mapping revealed key clusters such as digital transformation, challenges, and machine learning, reflecting emerging directions and innovation potential in technology-based religious learning. This study highlights opportunities for future research to enhance collaboration, promote innovation in digital religious education, and serve as a reference for ongoing studies in this increasingly vital field.